Investigation of clothes recycling as colouring agent for polypropylene-nanoclay nanocomposites - Othman, Mohd Hilmi; Muhammad, Arif Izzudin; Hassan, Sulaiman (KKG Publications, 2018)
Most of polymers can be recycled and reused to make new products or new inventions. Basically, some of the clothes were made up from polymer and it can be recycled as a compound or filler material in the process of injection moulding. The purpose of this research is to investigate the potential of recycling used clothes made from polyester, as a colouring agent for plastic product through the injection moulding process. This research started with shredding the used clothes into a powder and mixing the clothes powder with Polypropylene-Nanoclay Nanocom- posites (PPNC). The samples were produced in three different colours which were red, blue, and yellow according to the colour of the recycled cloth. All samples produced from this process went to several testing, such as tensile, warpage, shrinkage, and thermal analysis. According to the results, each of the samples produced the same colour as the used clothes which were red, blue, and yellow. Besides that, the highest value of Youngs Modulus for sample of used clothes was 525 MPa, which was better than the samples of unused clothes. The quality of the samples was better when the values of warpage and shrinkage were acceptable, which were in the range of 0.01 mm to 0.048 mm for warpage and 0.0141% to 0.0156% of shrinkage. Based on the thermal analysis, the peak temperature was 167.2 C which is not far different from pristine polypropylene. The outcome of this research should be beneficial in the future of plastic manufacturing process, in terms reducing cost of raw material and, at the same time, the environmental pollution impact also can be reduced.